Highly Efficient Synthesis of Multiantennary Bisected N‐glycans Based on Imidates. Issue 35 (22nd July 2016) - Mönnich, Manuel; Eller, Steffen; Karagiannis, Theodoros; Perkams, Lukas; Luber, Thomas; Ott, Dimitri; Niemietz, Mathäus; Hoffman, Joanna; Walcher, Janika; Berger, Lukas; Pischl, Matthias; Weishaupt, Markus; et al.
Abstract: The occurrence of N‐glycans with a bisecting GlcNAc modification on glycoproteins has many implications in developmental and immune biology. However, these particular N‐glycans are difficult to obtain either from nature or through synthesis. We have developed a flexible and general method for synthesizing bisected N‐glycans of the complex type by employing modular TFAc‐protected donors for all antennae. The TFAc‐protected N‐glycans are suitable for the late introduction of a bisecting GlcNAc. This integrated strategy permits for the first time the use of a single approach for multiantennary N‐glycans as well as their bisected derivatives via imidates, with unprecedented yields even in a one‐pot double glycosylation. With this new method, rare N‐glycans of the bisected type can be obtained readily, thereby providing defined tools to decipher the biological roles of bisecting GlcNAc modifications. Abstract : Bisecting á la carte : A general and robust modular approach to bisected N‐glycans was established based on a unified protecting‐group pattern. The switch to N‐TFAc protection of the donors for the antennae provides high yields for the difficult late‐stage introduction of a bisecting GlcNAc. Regardless of the number of antennae, a judicious choice of imidate activation permits the highly efficient one‐pot synthesis of bisected N‐glycans.